2017
DOI: 10.1080/09593330.2017.1365948
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic treatment of deinking sludge – effect on fibre and drainage properties

Abstract: This work focused on the enzymatic treatment of deinking sludge (DS), a waste stream arising from German deinked pulp mills. Three industrial DS samples were characterised with respect to chemical composition and fibre morphology. In this study, four cellulase enzyme preparations were tested under neutral pH conditions and one cellulase was identified as suitable for DS conditioning with no need of pH adjustment. Additionally, our approach shows that inorganic particles contained in the DS samples do not negat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…The hydrolysis yields by Opt CelMix and the different commercial cellulase preparations were then evaluated after 48 h. Comparable yields of about 90% were obtained by the Opt CelMix, Cellic CTec2 ® and Celluclast ® 1.5 L, while Viscozyme ® L displayed a yield of 26.4% (Figure 7B). High yields from the conversion of paper sludge by the commercial enzymes were expected as a recent study showed that Celluclast ® 1.5 L displayed a hydrolysis yield of 76.8% with the hydrolysis of deinking paper sludge [47]. Comparison of (A) hydrolytic rates after 6 h and (B) glucose yields obtained after 48 h from the hydrolysis of 2% (w/v, dry mass basis) paper sludge for 48 h at 50 °C using the Opt CelMix, Celluclast ® 1.5 L, Cellic ® CTec2 and Viscozyme ® L at a protein loading of 7.5 mg/g biomass.…”
Section: Comparison Of the Hydrolytic Efficiency Of The Opt Celmix To Commercial Cellulase Preparationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The hydrolysis yields by Opt CelMix and the different commercial cellulase preparations were then evaluated after 48 h. Comparable yields of about 90% were obtained by the Opt CelMix, Cellic CTec2 ® and Celluclast ® 1.5 L, while Viscozyme ® L displayed a yield of 26.4% (Figure 7B). High yields from the conversion of paper sludge by the commercial enzymes were expected as a recent study showed that Celluclast ® 1.5 L displayed a hydrolysis yield of 76.8% with the hydrolysis of deinking paper sludge [47]. Comparison of (A) hydrolytic rates after 6 h and (B) glucose yields obtained after 48 h from the hydrolysis of 2% (w/v, dry mass basis) paper sludge for 48 h at 50 °C using the Opt CelMix, Celluclast ® 1.5 L, Cellic ® CTec2 and Viscozyme ® L at a protein loading of 7.5 mg/g biomass.…”
Section: Comparison Of the Hydrolytic Efficiency Of The Opt Celmix To Commercial Cellulase Preparationsmentioning
confidence: 99%
“…The hydrolysis yields by Opt CelMix and the different commercial cellulase preparations were then evaluated after 48 h. Comparable yields of about 90% were obtained by the Opt CelMix, Cellic CTec2 ® and Celluclast ® 1.5 L, while Viscozyme ® L displayed a yield of 26.4% (Figure 7B). High yields from the conversion of paper sludge by the commercial enzymes were expected as a recent study showed that Celluclast ® 1.5 L displayed a hydrolysis yield of 76.8% with the hydrolysis of deinking paper sludge [47].…”
Section: Comparison Of the Hydrolytic Efficiency Of The Opt Celmix To Commercial Cellulase Preparationsmentioning
confidence: 99%
“…Breaking down of cellulose fibres in DIS by enzymes has been shown to not only add value to the feedstock, but also significantly reduce the water content and bulk of the sludge that has to be discarded (Steffen et al 2017a). Williams (2017) has studied three different types of paper sludge for ethanol production and has reported that usage of enzymes and break down of cellulose has significantly reduced the water holding capacity and increased the bulk density of all the three types of paper sludge.…”
Section: Substrate Characterizationmentioning
confidence: 99%
“…Enzyme performance at high pH values (8.6 in case of our substrate), typically associated with high amounts of mineral fillers present in DIS, is advantageous for many applications in the paper industry, as most of the current commercial cellulases perform best in weakly acidic conditions (pH 5-7) (Steffen et al, 2017a). Other factors that may affect stability and activity of enzymes produced on DIS are remaining organic pollutants or heavy metals (originating from inks).…”
Section: Screening Enzyme Activities Of Selected Strains On Dismentioning
confidence: 99%